Understanding the poisoning mechanisms of Si and Zr atoms on L12 Al3Ti (111) surface: A first-principles investigation. (April 2023) - Pang, Xingzhi; Yang, Loujiang; Yang, Jianbing; Pang, Mingjun; Xu, Zhengbing; Li, Anmin; Wei, Binglv; Tang, Hongqun
Abstract: In order to reveal the poisoning mechanism, the adsorption and diffusion of Si and Zr atoms on the L12 Al3 Ti (111) surface have been investigated using first-principles calculations. Based on the results of adsorption energy and work function, the most favorable adsorption sites for Si and Zr atoms are H4 and T1 of L12 Al3 Ti (111) surface, respectively. It is revealed from electron density differences, density of states and Mulliken population that the Ti–Si covalent bonds in Si@Al3 Ti(111) system the hybridization of Si 3p and Ti 3d orbitals while the Ti–Zr ionic bond in Zr@Al3 Ti(111) system is come from the contribution of Ti 3d and Zr 4d orbitals. By calculating formation energy, it is found that the Si and Zr atoms prefer to incorporate the Al site of the first layer and Ti site of the second layer of L12 Al3 Ti (111) surface, respectively. The energy barriers of Si and Zr atoms diffusion on or into L12 Al3 Ti (111) surface are also evaluated. Highlights: Si and Zr atoms adsorb preferentially at the H4 and T1 sites of L12 Al3 Ti (111) surface, respectively. The Si and Zr atoms prefer to incorporate the Al site of 1st layer and Ti site of 2nd layer of surface, respectively. The optimal pathways for Si and Zr atoms diffusion on L12 Al3 Ti (111) surface ware given. The diffusion barrier for different diffusion pathways were also predicted.